Hubungan Pekerjaan Ibu dan Pemberian Asi Eksklusif Dengan Kejadian Ispa Pada Balita Wilayah Kerja Puskesmas Tewah Kabupaten Gunung Mas - Aprilliana, Riska; Arifin, Syamsul; Permatasari, Silvani; Nurfianto, Sigit; Balyas, Abi Bakring (Barigas: Jurnal Riset Mahasiswa, 2025)
Acute Respiratory Tract Infection (ARI) is an acute infection that attacks the respiratory tract from the nose to the alveoli. There were 263 cases of ARI and in 2022, cases of ARI in toddlers increased to 540 in Tewah District, Gunung Mas Regency. This study aims to determine the relationship between maternal occupation and exclusive breastfeeding with the incidence of ARI in toddlers in the Tewah Health Center Work Area, Gunung Mas Regency. This study used an analytical observational method with a cross-sectional approach. Sampling was carried out using the purposive sampling method with the Slovin formula. A total of 30 samples that met the inclusion criteria were analyzed using the Spearman correlation test. This study was conducted in the Tewah Health Center Work Area in August-October 2023. The sample in this study were mothers who had toddlers and lived in the Tewah Health Center work area. The results of the study showed a relationship between maternal occupation and exclusive breastfeeding with ARI. There is no relationship between maternal occupation and the incidence of ARI in the Tewah Health Center Work Area. There is a relationship between Exclusive Breastfeeding and the incidence of ARI in the Tewah Health Center Work Area.